ANALISIS KARANGAN SISWA MORFOLOGI DALAM BAHASA INDONESIA DAN BAHASA MELAYU PATANI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the morphological features present in two essays written by Grade 5 Matayum students at Wittya Foundation School, Bandaon—one in Indonesian and the other in Patani Malay. The research specifically examines four core aspects of morphology, namely affixation, reduplication, word-formation processes, and cross-linguistic interference that emerges in students’ written production. Employing a descriptive qualitative design with content analysis, the study analyzes the linguistic structures produced by 20 students who were assigned to write two essays on the same theme, each in a different language. The essays were subsequently evaluated based on the morphological categories characteristic of Indonesian and Patani Malay. The results reveal that approximately 42% of the students produced incorrect forms in the use of the Indonesian prefix me-, generating nonstandard constructions such as memain, menjumpa, and melari. These deviations indicate strong cross-linguistic influence from Patani Malay, particularly in morphophonemic processes and affix selection. Conversely, the students’ Patani Malay essays demonstrated a high degree of morphological accuracy, reaching 96%, especially in the use of prefixes be- and ta-, the suffix -ko, and various reduplication patterns such as rumah-rumah and jalang-jalang. The comparison between the two languages shows that interference flows more dominantly from Patani Malay into Indonesian, affecting both affixation and lexical choices. These findings suggest that students possess stronger morphological competence in their mother tongue, whereas their Indonesian writing skills require systematic reinforcement. The study provides significant implications for developing effective instructional strategies in bilingual Patani Malay–Indonesian learning environments.